Diversity and distribution of Mexican pines, an overview - Sánchez-González, Arturo (Instituto de Ecología, A.C., 2016)
Mexico is considered a secondary center of diversity of the genus Pinus. Published literature indicates that this genus migrated from the north hemisphere through down natural corridors to the actual Mexican territory, forced by past climatic changes. The diversification of the genus happened on main mountain chains and those acted like biogeographical islands or biological corridors, modeling the actual distribution patterns of the Pinus in five mayor regions. Recently, forty six species, three subspecies and twenty two varieties from pines are recognized to Mexico. At least 55% from those species are endemic). Because of that, is the biggest diverse country of pine species from the world, with 42% of them. Mexican pines are one of the most valuable natural resources because of their traditional and commercial relevance and the environmental services that they provide. In spite of the national and regional significance, the continuous decreasing of covering areas from pine and pineoak forests because of the human activities and fire forest is alarming. At least 20 Mexican taxa are in some risk status and two of them: Pinus maximartinezii and P. muricata are classified like endangered species. National and international programs for sustainable use and conservation from Pinus are not efficient and sufficient yet.